Pseudogymnoascus destructans growth in wood, soil and guano substrates - Urbina, Jenny; Chestnut, Tara; Allen, Jennifer M.; Levi, Taal (Scientific Reports, 2021)
Understanding how a pathogen can grow on different substrates and how this growth impacts its dispersal are critical to understanding the risks and control of emerging infectious diseases. Pseudogymnoascus destructans (Pd) causes white-nose syndrome (WNS) in many bat species and can persist in, and transmit from, the environment. We experimentally evaluated Pd growth on common substrates to better understand mechanisms of pathogen persistence, transmission and viability. We inoculated autoclaved guano, fresh guano, soil, and wood with live Pd fungus and evaluated (1) whether Pd grows or persists on each (2) if spores of the fungus remain viable 4 months after inoculation on each substrate, and (3) whether detection and quantitation of Pd on swabs is sensitive to the choice to two commonly used DNA extraction kits. After inoculating each substrate with 460,000 Pd spores, we collected ~ 0.20 g of guano and soil, and swabs from wood every 16 days for 64 days to quantify pathogen load through time using real-time qPCR. We detected Pd on all substrates over the course of the experiment. We observed a tenfold increase in pathogen loads on autoclaved guano and persistence but not growth in fresh guano. Pathogen loads increased marginally on wood but declined ~ 60-fold in soil. After four months, apparently viable spores were harvested from all substrates but germination did not occur from fresh guano. We additionally found that detection and quantitation of Pd from swabs of wood surfaces is sensitive to the DNA extraction method. The commonly used PrepMan Ultra Reagent protocol yielded substantially less DNA than did the QIAGEN DNeasy Blood and Tissue Kit. Notably the PrepMan Ultra Reagent failed to detect Pd in many wood swabs that were detected by QIAGEN and were subsequently found to contain substantial live conidia. Our results indicate that Pd can persist or even grow on common environmental substrates with results dependent on whether microbial competitors have been eliminated. Although we observed clear rapid declines in Pd on soil, viable spores were harvested four months after inoculation. These results suggest that environmental substrates and guano can in general serve as infectious environmental reservoirs due to long-term persistence, and even growth, of live Pd. This should inform management interventions to sanitize or modify structures to reduce transmission risk as well early detection rapid response (EDRR) planning.